Priority Report: Rearrangements and Amplification of IER3 (IEX-1) Represent A Novel And Recurrent Molecular Abnormality In Myelodysplastic Syndromes (MDS) - Steensma, David P. (2009)
IER3 (formerly IEX-1) encodes a 27kDa glycoprotein that regulates death receptor-induced apoptosis, interacts with NF-κb pathways, and increases expression rapidly in response to cellular stresses such as irradiation. Animal models, gene expression microarray experiments, and functional studies in cell lines have suggested a potential role for IER3 in oncogenesis, but to date no abnormalities of IER3 at the DNA level have been reported in patients with neoplasia. Here we describe breakpoint cloning of a t(6;9)(p21;q34) translocation from a patient with a myelodysplastic syndrome (MDS), facilitated by conversion technology and array-based comparative genomic hybridization, which revealed a rearrangement translocating the IER3 coding region away from critical flanking/regulatory elements and to a transcript-poor chromosomal region, markedly decreasing expression. Using split-signal and locus-specific FISH probes, we analyzed 204 patients with diverse hematologic malignancies accompanied by clonal chromosome 6p21 abnormalities, and found 8 additional patients with MDS with IER3 rearrangements (translocations or amplification). While FISH studies on 157 additional samples from patients with MDS and a normal-karyotype were unrevealing, and sequencing the IER3 coding and proximal promoter regions of 74 MDS patients disclosed no point mutations, RT-PCR results suggested that dysregulated expression of IER3 is common in MDS (61% >4 fold increase or decrease in expression with decreased expression primarily in early MDS and increased expression primarily in later MDS progressing towards leukemia), consistent with findings in previous microarray experiments. These data support involvement of IER3 in the pathobiology of MDS.